A critical interpretation of ethnological and ethnomusicological narratives on Roma music in Serbia - Dumnić-Vilotijević Marija (Muzikologija)
This study presents research on Roma music in Serbia, as well as the socio-historical contexts that have shaped it. Texts by Tihomir Đorđević, Andrijana Gojković, Tatomir Vukanović, Vesna Acković, Dimitrije Golemović, Svanibor Pettan, Ivana Ljubinković, Alexander Marković, Ana Banić Grubišić, and other researchers who have contributed to this field from the beginning of the twentieth century to the present day are analyzed. Chronologically arranged thematic and disciplinary nodes are also highlighted - from ethnological descriptions, classifications and the first discussions on representations of Roma identity, through (musical) folkloristics, non-Roma ethnomusicological analytical engagement with understandable text (i.e., instrumental music), to the shifting of the Serbian and American anthropologists’ focus toward socially engaged interpretations.